Prototipo para orientación de personas con discapacidad Visual mediante una aplicación para móvil - Zambrano, Dannyll Michellc; Daza Álava, Yohanna Daniela; Pinargote Zambrano, José Daniel; Lituma Ramirez, Edgar Danilo (Revista Científica, 2019)
The present work describes the Design and elaboration of a prototype that by means of an algorithm links with a mobile application (App) and allows the orientation of visually impaired people implemented in the Faculty of Computer Science of the Technical University of Manabí; it consists of two parts, the mobile application which was developed in the programming environment Android Studio that allows detecting wireless signals (standard IEEE 802.11); the device detects certain pre-programmed signals at a certain distance will emit an audio that will be accompanied by a different vibration for each reference point indicating the sector in which it is circulating. The other part of the prototype are the reference points or access points, whose main component is a Wireless module (NodeMcu V3 LoLin), which through an algorithm emits signaling in the ISM band of 2.4 GHZ to mobile terminals. The reference points have energy autonomy of up to 20 hours from the alternating current supply by means of a photovoltaic panel in an automatic switching circuit.